COVID-19 pneumonia; predictors of severity and outcome in Erbil city hospitals - Fathulla Ahmed, Halgurd; Hussein, Zahir (Zanco Journal of Medical Sciences (ZJMS), 2023)
Background and objective: Corona infections disease nowadays is one of the major burden on national health institutes. The aim of the study is to identify the parameters that can predict the mortality in moderate to severely ill COVID-19 infected patients. Methods: A prospective cross sectional study was carried out in Erbil Hospitals, Kurdistan region/Iraq from December 2020 to December 2021 on a sample of 100patients with positive real-time polymerase chain reaction. The data of enrolled patients were collected by direct interview with patients or with their relatives and filled in a prepared questionnaire. The patients were followed up from their admission to hospital until their discharge alive or dead. Results: The mortality rate of hospitalized patients was 44% for 100 patients. Budesonide nebulizer were given to all of the patients. The mortality rate was significantly higher in old COVID-19 patients. The COVID-19 patients presented with dyspnea, hypertension and renal failure were significantly associated with higher mortality rates. High respiratory rate, low oxygen saturation and high C-reactive protein level were accompanied with higher mortality rates of COVID-19 patients. Conclusion: The early predictors of mortality in patients with moderate to severe COVID-19 infection were elderly age, clinical presentation of dyspnea, clinical co-morbidity with hypertension and renal failure, high respiratory rate, low oxygen saturation and elevated levels of C-reactive protein.